Rasch model analysis: Evaluating students' spatial thinking ability in higher-order thinking skills trigonometric comparison assessment (HOTS-TCA) - Ocy, Dwi Rismi; Rahayu, Wardani; Arthur, Riyan (Jurnal Gantang, 2024)
This study addresses the critical issue of insufficient spatial thinking abilities among students, which significantly affects their performance in higher-order thinking skills (HOTS) tasks, particularly in trigonometry. Focusing on 11th-grade students in Tanjungpinang, Indonesia, the research investigates how spatial thinking influences the ability to solve trigonometric comparison problems. Employing a mixed-method approach, the study integrates quantitative data from the Higher-Order Thinking Skills in Trigonometric Comparisons Assessment (HOTS-TCA) with qualitative insights from post-test interviews. Rasch Model Analysis evaluates the quality of an assessment instrument by providing measures of respondent abilities and item difficulties, fit statistics to ensure model alignment, reliability, and separation indices for consistency, a Wright Map for visualizing the relationship between skills and difficulties, and checks for unidimensionality and potential item bias to ensure fairness and validity. The Rasch analysis further confirms the reliability and validity of the HOTS-TCA instrument, highlighting its effectiveness in measuring spatial thinking across varying ability levels. The study finds that students with high spatial ability excel in visualizing geometric relationships but struggle with complex three-dimensional tasks. In contrast, medium-ability students have difficulties with mental manipulation and real-world applications, and low-ability students face significant challenges in basic visualization and interpreting geometric structures, leading to frequent misconceptions.